Asset management as a digital platform industry: a global financial network perspective - Haberly, D; Macdonald-Korth, D; Urban, M; Wójcik, D (Elsevier, 2019)
While contemporary technological disruption is increasingly conceptualized in terms of the logic and paradoxes of the digital platform economy, discussions of “FinTech” have only engaged to a limited extent with these debates—particularly from an economic geographic standpoint. Here we fill this gap by proposing an adapted Global Financial Network (GFN) framework for conceptualizing the organizational and geographic logic of the digital platform economy in finance, and applying it to examine the impact of the digital platform model on asset management. As we will show, asset management is being profoundly disrupted by what we dub digital asset management platforms—or DAMPs—which encompass services including index fund and ETF provision, robo-advising, and analytics and trading support. Like other digital platforms, DAMPs do not so much leverage technology to enhance their competitiveness within markets, as to radically restructure the market itself. Also, like other platforms, their rise has produced a winner-take-all paradox of centralization through democratization that defies predictions of technology-enabled industry decentralization. However, the logic and implications of the rise of DAMPs diverges, in other respects, from non-financial digital platforms, as finance has long possessed an informational intensity and regulatory and organizational fluidity characteristic of the digital platform economy. Consequently, the digital platform model has mostly developed endogenously in asset management through incremental innovation by major financial firms—in a process that has reinforced the position of leading incumbent asset management centers, and above all New York—rather than being introduced from the outside by upstart technology firms and clusters.